Challenges in evaluating surgical innovation. - Ergina, P; Cook, J; Blazeby, J; Boutron, I; Clavien, P; Reeves, B; Seiler, C; Altman, D; Aronson, J; Barkun, J; Campbell, W; Cook, J; et al. (2009)
Research on surgical interventions is associated with several methodological and practical challenges of which few, if any, apply only to surgery. However, surgical evaluation is especially demanding because many of these challenges coincide. In this report, the second of three on surgical innovation and evaluation, we discuss obstacles related to the study design of randomised controlled trials and non-randomised studies assessing surgical interventions. We also describe the issues related to the nature of surgical procedures-for example, their complexity, surgeon-related factors, and the range of outcomes. Although difficult, surgical evaluation is achievable and necessary. Solutions tailored to surgical research and a framework for generating evidence on which to base surgical practice are essential.